The Effect of ESG Disclosure, CSR Disclosure, and Firm Age on Abnormal Return with Firm Size as a Control Variable - Vina Aprilia Nursari; Khairunnisa (JURNAL MANAJEMEN MOTIVASI, 2026)
Governance (ESG) disclosure, Corporate Social Responsibility (CSR) disclosure, and firm age on abnormal return, with firm size as a control variable, in processed food companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative approach, secondary data were selected through purposive sampling and analyzed using panel data regression. The findings show that ESG disclosure has no significant effect on abnormal return, whereas CSR disclosure and firm age have significant effects. Firm age has a positive effect, CSR disclosure has a negative effect, and firm size has no significant effect. Keywords: Abnormal Return; ESG Disclosure; CSR Disclosure; Firm Age; Firm Size